Pembelian impulsif pada pembelanjaan online: peranan tipe kepribadian, kontrol diri, dan gender - Aulia, Rizky Meilani; Hanifah, Fithria Siti; Fridayanti (Universitas Brawijaya, 2024)
This research was conducted to determine the influence of three personality dimensions (Extraversion, Neuroticism, and Psychoticism) on impulse buying based on gender and the role of self-control as a moderator variable. The research method used is quantitative, with a sample of students from one of the Islamic Universities in Bandung. The measuring instruments used in this research were the Buying Impulsiveness Scale (BIS), Short-scale Eysenck Personality Question-Revised (EPQ-R), and Brief Self Control Scale (BSCS). This research had 254 respondents among students and e-commerce users, of which 173 were female. The results of this study revealed that self-control cannot moderate the influence between the three personality dimensions and impulsive buying in female and male students. Still, this research found a negative and significant impact on self-control on impulsive buying in female students, which can be interpreted as the higher self-control in female students, the lower their impulsive buying. Then, there is a positive and significant influence on the personality dimensions of Extraversion and Neuroticism on impulsive buying in male students, which means that the higher the dominance of the Extraversion and Neuroticism personality in male students, the higher the impulsive buying will be. This research proves that the factors that influence impulse buying are different between men and women.